Article RETRACTED due to manipulation by the authors and citations Results of Beginner Archery Skills Among Adolescents Based on Gender Review and Shot Distance - Destriani Destriani; Herri Yusfi; Destriana Destriana; Hendra Setyawan; José Vicente García-Jiménez; Francesca Latino; Francesco Tafuri; Tiok Wijanarko; Ari Wibowo Kurniawan; Khoiril Anam; Abdul Aziz Purnomo Shidiq; Muhammad Imam Rahmatullah; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to examine differences in scores resulting from beginner archery skills among teenagers based on gender (male & female) and shooting target distance factors (5 m, 10 m, & accumulated distances of 5 and 10 m). The sample for this research was 22 male and female students from classes XA, XB and XIA, taken using the cluster random sampling method. Data analysis used descriptive statistics and inferential factorial two-way anova. The mean score for male students at a shooting distance of 5 m was 57.82 and for female students was 49.36. The mean score for male students at a shooting distance of 10 m was 37.82 and for female students was 31.82. The mean score for male students at the accumulated shooting distance of 5 and 10 m was 59.18 and for females was 50.00. The results of the Anova test on the variable shot distance factor, Sig. value. 0.80 > 0.05 means there is no significant difference in archery skill results based on shooting distances of 5 m, and 10 m and accumulated 5 and 10 m. In the gender factor variable, the Sig. value. 0.325 > 0.05 means there is no significant difference in the results of archery skills based on male and female gender. Next, the variable factor of shooting distance and gender is the Sig. value. 0.985 > 0.05 means there is no influence or interaction between the factors of shooting distance and gender in determining the results of archery skills. The results of this research provide the conclusion that factors such as; training strategies and methods, experience, use of technology in training programs, and individual skill development are more crucial in improving archery skills among young beginners. Coaches and educators in the field of archery are advised to design inclusive and adaptive training programs, which do not focus too much on gender or shooting target distance as determining factors, but rather on developing individual skills and strengthening physical and mental aspects that support increased performance in archery.